Motivational interviewing to enhance treatment attendance in mental health settings: A systematic review and meta‐analysis - Lawrence, P.; Fulbrook, P.; Somerset, S.; Schulz, P. (Journal of psychiatric and mental health nursing, 2017)
Accessible summary What is known on the subject? Despite differences between samples, some literature reviews have suggested that MI is effective in enhancing treatment attendance for individuals with mental health issues. Little is known regarding the effects of MI as a pre‐treatment on individuals who are not seeking treatment for mental health issues. What this paper adds to existing knowledge? This systematic review of the literature and meta‐analysis demonstrates that MI is most beneficial for individuals who are not seeking mental health treatment. MI represents an opportunity for health promotion when patients are unmotivated but may otherwise be amenable to an intervention. MI is effective as a pre‐treatment intervention to motivate individuals to attend further post‐MI treatment and counselling. What are the implications for practice? MI is a process and a useful tool for clinicians in all therapeutic interactions, to motivate their patients to seek further assistance for mental heath issues. Health promotion and encouragement to attend further treatment sessions can be facilitated through telephone contact. Introduction The stages of change model suggests that individuals seeking treatment are in the “preparation” or the “action” stage of change, which is the desired outcome of successful Motivational Interviewing (MI) interventions. MI is known to enhance treatment attendance among individuals with mental health problems. Aim This study examined the published research on MI as a pre‐treatment to enhance attendance among individuals treatment‐seeking and non‐treatment‐seeking for mental health issues. Methods Fourteen randomized controlled trials were identified, and MI efficacy was examined dichotomously: attendance or non‐attendance for post‐MI therapy. Subgroup analysis investigated treatment‐seeking and non‐treatment‐seeking groups. Results Despite wide variations in sample sizes, blinding and monitoring, intervention fidelity was absent in the majority of published studies. Meta‐analysis revealed that MI pre‐treatment improved attendance relative to comparison groups. Conclusions Individuals not seeking treatment for mental health issues benefited the most from MI. Despite differences in MI treatment intensity, short interventions were as effective as longer interventions, whereas two MI sessions for as little as 15 min were effective in enhancing treatment attendance. Implications for Practice Motivational interviewing is a useful tool for clinicians in all therapeutic interactions to help motivate patients to seek assistance for mental health issues.